2021
DOI: 10.3389/fmicb.2021.708904
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cyclic Lipopeptides Fusaricidin Analogs for Treating Wound Infections

Abstract: Both acute and chronic cutaneous wounds are often difficult to treat due to the high-risk for bacterial contamination. Once hospitalized, open wounds are at a high-risk for developing hospital-associated infections caused by multi drug-resistant bacteria such as Staphylococcus aureus and Pseudomonas aeruginosa. Treating these infections is challenging, not only because of antibiotic resistance, but also due to the production of biofilms. New treatment strategies are needed that will help in both stimulating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Delayed wound healing with bacterial infections results in high treatment costs and increased morbidity [ 33 ]. Prevention of bacterial infections is an important priority in cutaneous wound management [ 34 ]. In this study, MRSA or P. aeruginosa was selected to represent two wide groups of Gram-positive and Gram-negative bacteria to establish the wide spectrum activity of the extract.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed wound healing with bacterial infections results in high treatment costs and increased morbidity [ 33 ]. Prevention of bacterial infections is an important priority in cutaneous wound management [ 34 ]. In this study, MRSA or P. aeruginosa was selected to represent two wide groups of Gram-positive and Gram-negative bacteria to establish the wide spectrum activity of the extract.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds comprised a guanidinylated β-hydroxy fatty acid and a cyclic hexapeptide. Paenibacillus stains produced various types of fusaricidins ( Gil et al, 2021 ), where enormous diversity exists even within those found in the same bacterial. MALDI-TOF MS is a practical technique for detecting secondary metabolites without additional purification, allowing the identification of active compounds in crude extracts via mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this peptide binds to bacterial genomic DNA to suppress the expression of the Panton-Valentine leukocidin and nuclease genes, which play major roles in S. aureus virulence. Gil et al [ 88 ] designed novel cyclic lipopeptides based on Fusarium analogues. The novel cyclic lipopeptide exhibited antimicrobial activity against MRSA in an in vivo porcine full-thickness wound model, resulting in a reduction in the bacterial count of approximately 3 log CFU/g and a slight increase in wound healing.…”
Section: Promising Strategies Against S Aureus Inf...mentioning
confidence: 99%